Signs of communicative competence of agricultural students - Semak, Liudmyla; Семак, Людмила Анатоліївна (Дніпровський державний аграрно-економічний університет, 2024)
Teaching students oral and written communication, i.e. communicative competence, is of exceptional importance in modern society. Due to the rapid decline of the general level of national linguistic culture in the mass media, fiction, journalism, and everyday communication, there is a need for mandatory formation of individual and personal motivations for mastering communicative competence among university students. Such a task in the system of higher education is implemented through the mandatory teaching of the discipline «Ukrainian language (for professional direction)». Навчання учнів усного та писемного мовлення, тобто комунікативної компетентності, має виняткове значення в сучасному суспільстві. Через стрімке падіння загального рівня національної мовної культури в засобах масової інформації, художній літературі, журналістиці, повсякденному спілкуванні виникає необхідність обов’язкового формування індивідуально-особистісних мотивацій до оволодіння комунікативною компетенцією серед студенти ВНЗ. Таке завдання в системі вищої освіти реалізується через обов’язкове викладання дисципліни «Українська мова (за професійним спрямуванням)».
Ознаки комунікативної компетентності студентів-аграрів
Keywords: agricultural students; студенти-аграрії; communicative competence; комунікативна компетентність; national language culture; національна мовна культура